2022
DOI: 10.1155/2022/8040656
|View full text |Cite|
|
Sign up to set email alerts
|

Study on Nursing Effect of Psychological Intervention on Uremic Hemodialysis Patients

Abstract: Aim. Patients in the hemodialysis stage are prone to psychological pressure of depression and anxiety and have resistance, which affects the clinical treatment effect. Effective psychological intervention plays a very important role in improving patients’ psychological pressure and patients’ compliance. The aim of this study is to explore the nursing effect of psychological intervention on uremic hemodialysis patients. Methods. There were 126 uremic hemodialysis patients admitted to the hospital from August 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…There is evidence that treating one symptom can produce a "crossover" effect and reduce the discomfort of other symptoms in the cluster [ 44 ]. For example, the mood symptom cluster is composed of multiple negative mood symptoms, which can be systematically solved through psychological relief [ 45 ]. In the cluster of skin discomfort symptoms, dry skin is a common symptom of patients (74.85%).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that treating one symptom can produce a "crossover" effect and reduce the discomfort of other symptoms in the cluster [ 44 ]. For example, the mood symptom cluster is composed of multiple negative mood symptoms, which can be systematically solved through psychological relief [ 45 ]. In the cluster of skin discomfort symptoms, dry skin is a common symptom of patients (74.85%).…”
Section: Discussionmentioning
confidence: 99%
“… 14 Early and appropriate diagnosis of depression in ESRD patients is crucial for improving treatment adherence and quality of life. 14 , 15 Therefore, health care professional caring for HD patients should be qualified to regularly assess and investigate depression, facilitating promptly referral to psychologists for early treatment. 3 , 5 Recent studies highlight the positive impact of early nursing screening, psychological support, and nursing intervention in the treatment compliance, quality of life, and the reduction of anxiety, depression and risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 5 Recent studies highlight the positive impact of early nursing screening, psychological support, and nursing intervention in the treatment compliance, quality of life, and the reduction of anxiety, depression and risk of complications. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Psychological intervention refers to the planned implementation of psychological counseling for patients in order to help them reduce psychological pressure and complete the predetermined goal. 9 Previous studies have reported that psychological intervention could help improve DTC patients’ QoL. In 2016, Wu et al 10 reported that a 1-year psychological and behavioral intervention could improve functional capacities and QoL, alone with reducing depression and anxiety in patients with DTC who treated with postoperative radioactive iodine.…”
Section: Introductionmentioning
confidence: 99%